Effects Of Chromium Yeast Supplementation On Haematological Parameters In Chicken - Malathi, V.; Naik, Jaya; Gowda , N.K.S.; Reddy , K. Venkata (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A biological trial was conducted to study the effect of supplementing chromium yeast in chicken on haematological parameters. 400 chicks were allocated into four groups with 100 chicks in each treatment. Group I was fed with basal diet and groups 2, 3 and 4 were fed with basal diet added with 200, 400 and 600 ppb Cr yeast. Blood analysis revealed that supplementation of Cr yeast significantly increased Hb%, Total cell counts, lymphocytes and reduced heterophils and heterophil to lymphocyte ratio. Other haematological parameters viz., TEC, PCV, MCV, MCH, MCHC and platelet counts were unaffected by Cr yeast supplementation. These results indicate that Cr yeast is beneficial in improving immune response and also increasing Hb and TC, thereby alleviating stress in chicken.
Keywords: Chicken; Haematology; Haemoglobin; Immunity; Lymphocyte